Effects of dump site soil on the leaf structures of Luffa cylindrical (sponge gourd) and Amaranthus viridis (green amaranth) - S.I. Musa; K.O. Awayewaserere; K.I. Njoku (Journal of Applied Sciences and Environmental Management)
Previous researches have shown the presence of heavy metals (HMs) such as lead (Pb) at different levels in Olusosun dumpsite, Lagos. This study aimed at finding out if the anatomical differences found in Luffa cyclindrical and Amaranthus viridis grown on the dumpsite is an indication of the HMs and also determine the distribution of HMs on the dumpsite. The results showed the HMs detected in the dumpsite soil at three spots were significantly higher than the control (p=0.5). The concentrations of HMs were in sequence for soils A: Pb>Zn=Cr>Fe>Cu>Ni. Spot B: Fe>Cr>Pb>Zn>Cu>Ni, spot C: Fe>Pb>Cr>Zn>Cu>Ni and Control: Pb>Fe>Zn>Cu>Ni. All the HMs detected at the three spots and control were below the World Health Organization (WHO) and Dutch pollutant standard level, except for (Zn) which was at the exact limit (50.000Mg/kg). The plants obtained from both the dumpsite and control sites didn’t show marked visible morphological changes. However, anatomical changes in the leaves epidermis such as irregular shape of the epidermis, absence of trichomes and decrease in quality and stomata size were all witnessed in the dumpsite plant as against the control. Hence, it is likely that all detected differences in the epidermal structures of the test plant grown on dumpsite soil were caused by the high level of HMs present in the dumpsites and therefore suggested that, changes in epidermal structures of L. cyclindrical and A. viridis grown on Olusosun dumpsite soils is an indication of HMs such as Zn and Pb present.